The Dialectic of a Global Language (GIST – Education and Learning Research Journal, 2007)
This essay attempts to answer some of the basic assumptions made about English as a global language. It is argued that such assumptions, especially those concerning political and economic power, are not sufficient in themselves to explain why English has acquired such global importance. Rather, what has greatly contributed to the possibility for any language to become global has been a change in the nature of language itself, a change which made language more standardized and uniform than it had ever been before. Also this relates to how this process of standardization led to changes in how text was produced, and as a result changes in how reading would take place. Such changes pre-empted and made possible the later invention of the printing press. How language from then on became organized and stored meant that it would be easier to teach and learn, and as a consequence reproduced in a more standardized and uniform way. This essay, in turn, concludes by pointing out that because of this process of standardization, any language in the world can be a global one, not just English. However the case does not 50 end there. In what is a post-script to this essay, it is argued how political and economic class based factors rather than encouraging the spread of English in countries not of its origin, actually restrict it. Hence this undermines the efficacy of any pedagogical method which has been greatly enhanced by the growing standarization and uniformity of languages in the modern world.